Prejunctional muscarinic (M1)-receptor interactions on guinea-pig ileum: lack of effect of cisapride. - Schuurkes, J. A. (1988)
1. Cisapride stimulates gastrointestinal motility, probably by enhancing the release of acetylcholine from myenteric nerve endings. Such an effect could be mediated via presynaptic muscarinic (M1)-receptors. Our aim was to determine whether cisapride could antagonize the inhibitory effects of a M1-agonist, McN-A-343 or mimic the effects of a M1-antagonist, pirenzepine. 2. Longitudinal segments were suspended in Krebs solution (95% O2, 5% CO2, 37.5 degrees C) for isometric tension recording (preload 1 g) during electrical transmural stimulation (0.1 Hz, 1 ms, sub- or supramaximal current). 3. McN-A-343 (2.0 x 10(-6) M) reduced the contractile response to supramaximal stimulation (EC50 = 1.6 x 10(-6) M), but had no effect on the contractions induced by exogenous acetylcholine. 4. The inhibitory effect of McN-A-343 on the contractile response to electrical stimulation could be reversed by pirenzepine (EC50 = 1.6 x 10(-8) M) but not by atropine. At these concentrations pirenzepine itself did not modify the contractile response to electrical stimulation. However, at 50 times higher concentrations pirenzepine inhibited the response to electrical stimulation as well as the response to exogenous acetylcholine (EC50 = 8.5 x 10(-7) M). 5. Cisapride enhanced the contractile response to submaximal electrical stimulation by 49 +/- 10%. This stimulating effect of cisapride was not affected by the presence of pirenzepine but was reduced in the presence of McN-A-343 (22 +/- 7%). 6. In conclusion: the effects of McN-A-343 and pirenzepine on the electrically stimulated guinea-pig ileum are compatible with an interaction on presynaptic muscarinic-(M1)-receptors. Cisapride enhances the twitch amplitude via mechanisms independent of such M1-receptor interactions.